Pendekatan Pemasaran dalam Meningkatkan Efisiensi Pembiayaan Terpadu Pada Pesantren Salafiyah - Nurhidayati, Indah; Sulistyowati; Safitri, Yuni; Izzah, Khoirotul (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The purpose of this study is to find out; What is the marketing strategy towards integrated financing management and what are the supporting and inhibiting factors in carrying out the Marketing Strategy towards Integrated Financing Management at the Independent Islamic Boarding School. This study uses a descriptive qualitative research method. The research was conducted at the Independent Islamic Boarding School, Salafiyah Al Miftah Puncu Kediri, East Java. The results of this study; 1) The Marketing Strategy towards Integrated Financing Management at the Independent Islamic Boarding School is carried out through socializing and introduced to the general public. In carrying out integrated financing management, this pesantren uses human resources and existing potential as a source of financing so that it does not require too much money from the government or costs from students who are too expensive. 2) One of the components that support the implementation of the Marketing Strategy towards Integrated Financing Management is budgeting (budget), which includes the preparation of an Expenditure Revenue Budget Plan. The second is accounting. At the Al-Mawaddah Kudus hut, counting is carried out using a postal book (vatebook), invoices, cash books, check sheets, journals, and ledgers. The third, the examination, or examination, still relates to the accountability of the treasurer for the receipt, storage, and payment or surrender of money to the authorities